2020
DOI: 10.1007/s11356-020-09858-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ammonia and hydrogen sulfide emissions from a commercial dairy farm with an exercise yard and the health-related impact for residents

Abstract: Airborne emissions from concentrated animal feeding operations (CAFOs) have the potential to pose a risk to human health and the environment. Here, we present an assessment of the emission, dispersion, and health-related impact of ammonia and hydrogen sulfide emitted from a 300-head, full-scale dairy farm with an exercise yard in Beijing, China. By monitoring the referred gas emissions with a dynamic flux chamber for seven consecutive days, we examined their emission rates. An annual hourly emission time serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…H 2 S is a chemically unstable reducing agent, easily oxidised, and produces toxic sulphuric byproducts upon combustion (Habeeb et al, 2017). It has been reported that NH 3 and H 2 S emissions can pose a health risk, given their malodorous and hazardous properties, contributing to ecosystem acidification (Wu et al, 2020). Our findings in Exp.…”
Section: Discussionmentioning
confidence: 51%
“…H 2 S is a chemically unstable reducing agent, easily oxidised, and produces toxic sulphuric byproducts upon combustion (Habeeb et al, 2017). It has been reported that NH 3 and H 2 S emissions can pose a health risk, given their malodorous and hazardous properties, contributing to ecosystem acidification (Wu et al, 2020). Our findings in Exp.…”
Section: Discussionmentioning
confidence: 51%
“…However, emissions measure using open‐path techniques at this dairy were much higher than those estimated from flux chamber measurements for both winter and summer, with mean winter emissions greater by a factor of 52 and mean summer emissions greater by a factor of 53. Mean spring emissions for the entire dairy were also much higher (by a factor of 38) than short‐term May H 2 S emissions of the feedlot pen in China (Wu et al., 2020). However, summer mean emissions of the entire dairy were much less than the 2,883 g H 2 S d −1 m −2 reported for a Texas cattle feedlot (Baek et al., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Emissions of the corral surface of a Texas dairy, assessed using flux chambers, had similar summer and winter emissions, averaging 22.3 g H 2 S d −1 hd −1 (Muktar & Mutlu, 2008). Flux chamber measurements of H 2 S emissions of the surface of a feedlot pen of a Chinese dairy in May averaged 0.085 g H 2 S d −1 hd −1 (Wu et al., 2020). Similar flux chamber measurements of H 2 S emissions of a Texas feedlot surface over 8 d in August were lower than these open dairy lots, ranging from 0.011 to 0.039 g H 2 S d −1 hd −1 (Baek et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since there are limitations of water resources in the High Plains where most feedlots are located, potential alternative options need to be studied for PM emission control. It is worth noting that gaseous pollutants, i.e., NH 3 , hydrogen sulfide, and VOC along with GHGs are also largely emitted from the CAFOs alongside PM, causing air quality issues in the atmosphere [ 45 ]. Reasonably, it is important to conduct more experiments on the gaseous pollutants using advance technologies for simpler emission monitoring and quicker control actions.…”
Section: Resultsmentioning
confidence: 99%